(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the content, importance of integration in teaching special and general professional subjects and its role in increasing educational efficiency. Forms and methods of integrated education, mechanisms for ensuring interdisciplinary connections, and pedagogical aspects of their implementation in practice are covered. Also, the issues of developing professional competencies in students and combining theoretical knowledge with practical activities based on integration are considered.